Citizen Centered Approach to Preventing Violent Extremism: A Case of Somaliland - Adad, Mohamoud Saed (Eximia, 2023)
The Horn of Africa region has been tackling prolonged ideology-based extremism for over two decades. Several factors are believed to have fueled the rise of extremism in the region, including but not limited to poverty, marginalization, lack of youth engagement, limited integration among regional states, limited access to formal education, and religious misconceptions. Somaliland, which is internationally part of Somalia but declared independence and regulated itself for the last 30 years; has succeeded in controlling both extremism and other forms of violence such as the pirates with a unique approach to citizens' engagement as a community policing. Violent extremism massively penetrated the region with its strong base in Somalia. Despite progress in countering and preventing violent extremism with regional effort and international community support, there is no single strategy and best practices applied by all regional governments to prevent violent extremism. Therefore, this paper will assess the new paradigm of prevention with the Somaliland approach of citizen engagement and how these elements contributed prevention of extremism spread across the border to neighboring countries and beyond. This study will employ a Trust-Based, Qualitative Methodology developed by ICEPCVE. The reason is to assess the impacts of National and Regional Efforts in Countering and Preventing Violent Extremism explicitly and accurately. This paper will unpack Somaliland's approaches to tackling these global and regional challenges of violent extremism and the secret of stability for more than 30 years, what other countries can learn about it, and how with thoughtful recommendations.